Carbon monoxide-releasing properties and DFT/TDDFT analysis of [Mn(CO)3(bpy)L]PF6 type novel manganese complexes - Üstün, E.; Koç, Ş.; Demir, S.; Özdemir, I. (2016)
Novel manganese(I)carbonyl complexes of the general formula [Mn(CO)3(bpy)L]PF6 (bpy = 2,2-bipyridyl, L = N-(2-methylbenzyl)imidazoline, N-(3-methylbenzyl)imidazoline, N-(4-methylbenzyl)imidazoline, N-(2,4,6-trimethylbenzyl)imidazoline) were synthesized and characterized by analytical (LC-MS spectrometry and elemental analysis) and spectroscopic (1H NMR, 13C NMR, cosy2D-NMR, infrared) methods. The CO-releasing properties of these complexes were investigated with myoglobin assay. The DFT/TDDFT calculations were made by ORCA package program with both BP86 and B3LYP functionals. © 2016 Elsevier B.V. All rights reserved.